International Academic Symposium of Social Science 2022 2022
DOI: 10.3390/proceedings2022082030
|View full text |Cite
|
Sign up to set email alerts
|

Software Reuse Practices among Malaysian Freelance Developers: A Conceptual Framework

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(96 reference statements)
0
0
0
Order By: Relevance
“…Software reuse practices have also evolved, as Makitalo et al, (2020) redefined it as opportunistic reuse that involves the development of software using software components that were originally not made to work together due to the advancement of ICT and software development platforms (Zhou, 2020). Although certain developers have overlooked reuse practices due to a lack of expertise (Bakar & Kasirun, 2014), incomplete documentation (Jusoh, Gorment, Nor, Nor, & Muhammad, 2017;Ahmad, Ubaidullah, & Lakulu, 2014), and difficult to maintain (Baharom, Deraman, & Hamdan, 2014), recent studies have shown that freelance developers have the expertise, experience, knowledge, skills, and self-efficacy to deploy this method (Osman, Masrek, & Wahid, 2022), thus offering attractive solutions for software development jobs. In the post-COVID-19 era, more developers tend to work as freelancers due to high salaries and work flexibility (Rauf, Petre, Tun, Lopez, & Nuseibeh, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Software reuse practices have also evolved, as Makitalo et al, (2020) redefined it as opportunistic reuse that involves the development of software using software components that were originally not made to work together due to the advancement of ICT and software development platforms (Zhou, 2020). Although certain developers have overlooked reuse practices due to a lack of expertise (Bakar & Kasirun, 2014), incomplete documentation (Jusoh, Gorment, Nor, Nor, & Muhammad, 2017;Ahmad, Ubaidullah, & Lakulu, 2014), and difficult to maintain (Baharom, Deraman, & Hamdan, 2014), recent studies have shown that freelance developers have the expertise, experience, knowledge, skills, and self-efficacy to deploy this method (Osman, Masrek, & Wahid, 2022), thus offering attractive solutions for software development jobs. In the post-COVID-19 era, more developers tend to work as freelancers due to high salaries and work flexibility (Rauf, Petre, Tun, Lopez, & Nuseibeh, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In the post-COVID-19 era, more developers tend to work as freelancers due to high salaries and work flexibility (Rauf, Petre, Tun, Lopez, & Nuseibeh, 2023). Renowned as highly skilled and wealthy experience across software development phases (Osman et al, 2022), the creative and innovative solutions offered by freelancers were too good for software development organizations to overlook (Sison & Lavilles, 2018). This is a crucial aspect of development, as Rangasamy, Negaraj, and Nandhakumar (2021) highlighted that nowadays, software must have high quality to cater to many users and achieve development efficiency to market the software quickly.…”
Section: Introductionmentioning
confidence: 99%